Genetic Evidence for the Role of the Vacuole in Supplying Secretory Organelles with Ca2+ in Hansenula polymorpha. - Anastasia V Fokina; Maria B Chechenova; Azamat V Karginov; Michael D Ter-Avanesyan; Michael O Agaphonov (PLoS ONE, 2015)
Processes taking place in the secretory organelles require Ca2+ and Mn2+, which in yeast are supplied by the Pmr1 ion pump. Here we observed that in the yeast Hansenula polymorpha Ca2+ deficiency in the secretory pathway caused by Pmr1 inactivation is exacerbated by (i) the ret1-27 mutation affecting COPI-mediated vesicular transport, (ii) inactivation of the vacuolar Ca2+ ATPase Pmc1 and (iii) inactivation of Vps35, which is a component of the retromer complex responsible for protein transport between the vacuole and secretory organelles. The ret1-27 mutation also exerted phenotypes indicating alterations in transport between the vacuole and secretory organelles. These data indicate that ret1-27, pmc1 and vps35 affect a previously unknown Pmr1-independent route of the Ca2+ delivery to the secretory pathway. We also observed that the vacuolar protein carboxypeptidase Y receives additional modifications of its glycoside chains if it escapes the Vps10-dependent sorting to the vacuole.